Autism and psychopathology - prevalence, identification, and symptoms equivalence: study protocol - Bertelli, Marco O.; Bianco, Annamaria; Deb, Shoumitro; Scuticchio, Daniela; Kaleci, Shaniko; Scattoni, Maria Luisa (Frontiers in Psychiatry, 2024)
Despite increasing evidence of high psychopathological vulnerability in people with Autism Spectrum Disorder (ASD) and/or Intellectual disability (ID), comprehensive data on prevalence and presentation of psychiatric disorders (PD) in people with significant cognitive and communication impairment are lacking. The extent to which PD can present with behavioural/observable symptoms and include Problem Behaviours (PB) has also been scarcely evaluated through population-based studies. The paper presents the protocol of a cross-sectional study aimed at filling these gaps, referred to a large multicentric Italian population-based sample of adolescents and adults.A battery of validated scales, SPAIDD, DASH-II, DiBAS-R, and STA-DI, is used to support and control for clinical diagnoses of PD. Study population is stratified according to different independent variables such as the severity of ID and ASD, gender, age group, and source of recruitment. A network analysis will be carried out to identify the most central behavioural symptoms for the various PD and their relationship with PB. Overlap between psychiatric symptoms and ASD and ID phenotypes is also addressed.This study should provide valuable insight into better diagnostic accuracy, leading to well-informed interventions to improve the quality of life of people with ASD and/or ID.